1999
DOI: 10.1063/1.125295
|View full text |Cite
|
Sign up to set email alerts
|

Optical switching of nematic liquid crystal by means of photoresponsive polyimides as an alignment layer

Abstract: Photosensitive polyimides (PIs) as an alignment layer induced optical switching of nematic liquid crystal (NLC) on photoirradiation at 366 nm. The orientation of NLC molecule was changed from homogeneous to homeotropic alignment on photoirradiation with a dc electric field as a bias. The optical switching behavior of NLC was largely affected by the chemical structures of PIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Since the transmittance recovers when irradiation is stopped, it is assumed that the optical switching is based on an alignment change between a homogeneous state and a homeotropic state. [ 33 ] Recently, aromatic PIs exposed to LPL with a longer wavelength were reported to show a high effi ciency of photoalignment without any signifi cant change in chemical structures of PIs. [ 34 ] To evaluate the alignment, a PI fi lm formed on a glass substrate was irradiated with LPL at 366 nm, and then an LC cell was fabricated with two pieces of these exposed PI-coated substrates, sandwiching with 5CB between them.…”
Section: Photoactive Pimentioning
confidence: 99%
See 1 more Smart Citation
“…Since the transmittance recovers when irradiation is stopped, it is assumed that the optical switching is based on an alignment change between a homogeneous state and a homeotropic state. [ 33 ] Recently, aromatic PIs exposed to LPL with a longer wavelength were reported to show a high effi ciency of photoalignment without any signifi cant change in chemical structures of PIs. [ 34 ] To evaluate the alignment, a PI fi lm formed on a glass substrate was irradiated with LPL at 366 nm, and then an LC cell was fabricated with two pieces of these exposed PI-coated substrates, sandwiching with 5CB between them.…”
Section: Photoactive Pimentioning
confidence: 99%
“…Ikeda et al studied a dynamic photocontrol of LC alignment, optical switching of nematic LCs using a photo active PI containing a benzophenone moiety as an alignment layer. [ 33 ] An LC cell with a gap of 5 μ m, in which both substrates were coated with rubbed PI fi lms, was fabricated to evaluate the photoresponse of a nematic LC (5CB). The change in transmittance as a function of applied voltage for the LC cell is shown in the left of Figure 3 C, in which the threshold voltage for the electric Freedericksz transition is quite different between the irradiated and unirradiated samples.…”
Section: Photoactive Pimentioning
confidence: 99%
“…27). 169 An LC cell with a gap of 5 mm, in which substrates were coated with PI films and then rubbed, was fabricated to evaluate an optical response of 5CB. Fig.…”
Section: Changes In Alignment Of Lcs By Photoactive Surface Layersmentioning
confidence: 99%
“…However, this method is accompanied by chemical reactions, resulting in weakening the thermal stability of PIs due to serious degradation of backbone structures. Ikeda et al studied a dynamic photocontrol of LC alignment, optical switching of nematic LCs using a photo­active PI containing a benzophenone moiety as an alignment layer 33. An LC cell with a gap of 5 μm, in which both substrates were coated with rubbed PI films, was fabricated to evaluate the photoresponse of a nematic LC (5CB).…”
Section: Lmwlc Actuatorsmentioning
confidence: 99%
“…It was found that photo­irradiation at 366 nm results in an immediate change in transmittance when a bias voltage of 4.5 V is applied across the LC cell. Since the transmittance recovers when irradiation is stopped, it is assumed that the optical switching is based on an alignment change between a homogeneous state and a homeotropic state 33…”
Section: Lmwlc Actuatorsmentioning
confidence: 99%